Genome-wide reconstruction of the metabolic network of Phaeodactylum tricornutum - Sharaf, Hazem (AUC Knowledge Fountain, 2014)
With the advent of high-throughput genome sequencing, metabolic network reconstructions gained prominence as the de facto standard of attaining a holistic approach towards the understanding of an organism's metabolism. A reconstructed network supplemented with genome annotations and literature mining is turned into a knowledgebase on the organism. Such a network serves as powerful predictive tool for the state of metabolism by applying flux balance analysis (FBA) which is based on a mathematical linear optimization approach. The advantages of FBA are to derive insights about the metabolic phenotype of an organism and to direct metabolic engineering for further capabilities. This has been demonstrated through numerous experiments with several organisms and has led to expanding biotechnological applications such as advanced strain design and discovery of drug targets. Diatoms are photosynthetic eukaryotic algae that inhabit aquatic environments worldwide. They are responsible for more than one fifth of the global organic carbon production and half of the photosynthetic activity in the world oceans. In addition, they have a cell wall made of silica, which sends them to the bottom of the ocean floor upon their death, stressing their critical role in geochemical cycles of the oceans. They also accumulate up to half of their dry weight in lipids when under stress, making them a potential source for biofuels. The pennate Phaeodactylum tricornutum is one of only two diatoms with a complete genome sequenced and published until now, and whose genome has revealed novel metabolic pathways in nitrogen and carbon assimilation. This work presents the first thorough genome-scale metabolic reconstruction for a diatom, which incorporates 947 reactions catalyzed by 869 genes. In-silico simulations of the model through FBA have revealed the first insights into the carbon fixation pathways and the metazoan-like urea cycle. It also includes the first pathway reconstructions of diatom-specific metabolites such as the carbohydrate chrysolaminarin and carotenoid fucoxanthin. This model serves as a platform for the design of future biotechnological applications in diatoms.